2021
DOI: 10.1002/brb3.2068
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficit is correlated with sleep stability in insomnia: A cardiopulmonary coupling study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…They found increased LFC and a lower HFC/LFC ratio among the insomnia group ( Schramm et al, 2013 ). Zhang et al (2021) studied insomnia patients with cognitive impairment and found decreased HFC indicating predominance of unstable sleep compared to insomnia patients with normal cognition. However, Jarrin et al (2016) found that improvements in some sleep parameters in insomnia patients subjected to 6 weeks of cognitive behavior therapy was associated with decreased HFC.…”
Section: Cardiopulmonary Coupling In Other Sleep Disordersmentioning
confidence: 99%
“…They found increased LFC and a lower HFC/LFC ratio among the insomnia group ( Schramm et al, 2013 ). Zhang et al (2021) studied insomnia patients with cognitive impairment and found decreased HFC indicating predominance of unstable sleep compared to insomnia patients with normal cognition. However, Jarrin et al (2016) found that improvements in some sleep parameters in insomnia patients subjected to 6 weeks of cognitive behavior therapy was associated with decreased HFC.…”
Section: Cardiopulmonary Coupling In Other Sleep Disordersmentioning
confidence: 99%
“…The pathogenesis may be related to increased sympathetic activity, dysregulation of the hypothalamic-pituitary axis, and increased inflammation ( Javaheri and Redline, 2017 ). Moreover, insomnia is considered a risk factor for HTN ( Cappuccio and Miller, 2017 ; Bathgate and Fernandez-Mendoza, 2018 ), cognitive impairment ( Irwin and Vitiello, 2019 ; Zhang et al, 2021 ), obesity, and diabetes ( Knutson et al, 2017 ; Mokhlesi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%